Systematic Literatur Review: Penggunaan Media Digital Berbasis Etnomatematika untuk SMP - Say-in Yasha; Dwi Sulistyaningsih; Venissa Dian Mawarsari (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study intends to assess the validity of the media and methods used in developing digital learning tools based on ethnomathematics for junior high schools. The research employed the Systematic Literature Review (SLR) method. The review followed the PRISMA guidelines by collecting articles through Publish or Perish with sources from Google Scholar within the period of 2020–2025. The keywords used were “ethnomathematics” and “digital media.” From the selection process, 15 articles were found to meet the inclusion criteria articles were identified as meeting the inclusion criteria. Based on the analysis, it was revealed that digital media such as electronic modules (e-modules), electronic student worksheets (E-LKPD), digital comics, educational videos, interactive PowerPoint presentations, and Android-based applications effectively integrated mathematical concepts (geometry, geometric transformations, and circles) with local cultural elements such as batik motifs, traditional houses, and handicrafts. These media demonstrated a high level of validity, all categorized as feasible, practical, and effective. The analyzed articles reported average validity scores (≥ 76%), practicality (≥ 80%), and effectiveness in improving learning mastery up to 81.00%. The use of such media enhanced students’ mathematical understanding, communication skills, and cultural appreciation through interactive features. This study provides insights into the types of digital formats most frequently utilized at the junior high school level.